Irish Genealogy Tourism in a Globalised World: An Analysis of Contemporaiy Trends in County Galway - Gergelyova, Marta; McCarthy, Mark; Nielsen, Monica (Turyzm/Tourism, 2008)
This paper is concerned with the challenges now faced by genealogy tourism in County Galway, situated on Ireland’s western seaboard. It presents, in a condensed format, the results of fieldwork which combined qualitative and quantitative methodologies, namely recorded focus group and one-to-one interviews (23 interviewees), participant observation (6 participants), diaries (2 participants) and questionnaires (302 respondents). This assisted in producing a comprehensive cross-sectoral snapshot of genealogy tourism in the region and has enabled us to tackle three pertinent questions: what are the reasons behind the 50% decline in the overall number of genealogy tourists visiting Ireland since 2000?; what are the profiles, needs and expectations of genealogy tourists coming to Ireland and how do they differ from those of mainstream tourists?; can the genealogy tourism market be recovered and - if yes - how can this be achieved? Finally, the investigation brought fresh perspectives on marketing Irish genealogy and incorporating it into new heritage tourism products that respect local needs but respond to the competitive environment of a globalised world in which the tourism industry continuously redefines its roles.